Government Guarantees : Allocating and Valuing Risk in Privately Financed Infrastructure Projects. (World Bank Group, 2007)
The book considers when governments should give guarantees to private investors. After describing the history of guarantees, and the challenges the politics and psychology create for good decisions, the book sets out principles for allocating risk (and therefore guarantees), techniques for valuing guarantees, and rules to encourage good decisions.